Inflammation and Depression: A Nervous Plea for Psychiatry to Not Become Immune to Interpretation - Jan Pieter Konsman (MDPI AG, 2019)
The possibility that inflammation plays a causal role in major depression is an important claim in the emerging field of immunopsychiatry and has generated hope for new treatments. The aims of the present review are first to provide some historical background and to consider the evidence in favor of the claim that inflammation is causally involved in major depression. The second part discusses some of the possibilities allowed for by the use of broad ‘umbrella’ concepts, such as inflammation and stress, in terms of proposing new working hypotheses and potential mechanisms. The third part reviews proposed biomarkers of inflammation and depression and the final part addresses how elements discussed in the preceding sections are used in immunopsychiatry. The ‘umbrella’ concepts of inflammation and stress, as well as insufficiently-met criteria based inferences and reverse inferences are being used to some extent in immunopsychiatry. The field is therefore encouraged to specify concepts and constructs, as well as to consider potential alternative interpretations and explanations for findings obtained. The hope is that pointing out some of the potential problems will allow for a clearer picture of immunopsychiatry’s current strengths and limitations and help the field mature.